Lanskap Pemikiran Hadis di Amerika: Gagasan Jonathan A.C Brown tentang Kritik Matan - Tumewu, Noufal P.; Ismail, Padli (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2022)
This paper attempts to review the landscape of hadith development in America and focuses on one of the ideas that examines the study of hadith text criticism by Jonathan A.C Brown in his article The Rules Matn Criticism: There Are No Rules. Exploring how Brown criticizes hadith text studies which in his view have received less attention from scholars and Islamic researchers, the results of this review show that the criticism presented by Brown leads to the absence of methodologically determined criteria for matan criticism. He proves this by giving examples of several scholars who reject hadiths that are considered flawed in terms of matan, but at other times take hadiths that according to Brown have the same flaws. This uncertainty is what makes Brown assume that scholars and researchers pay less attention to matan studies compared to sanad studies which are considered more important in determining the quality of a hadith. This review uses a library research type of research by looking at Brown's ideas through several of his statements related to hadith studies.